2015
DOI: 10.1242/jcs.160051
|View full text |Cite
|
Sign up to set email alerts
|

Subnuclear domain proteins in cancer cells support transcription factor RUNX2 functions in DNA damage response

Abstract: Cancer cells exhibit modifications in nuclear architecture and transcriptional control. Tumor growth and metastasis are supported by RUNX family transcriptional scaffolding proteins, which mediate the assembly of nuclear-matrix-associated generegulatory hubs. We used proteomic analysis to identify RUNX2-dependent protein-protein interactions associated with the nuclear matrix in bone, breast and prostate tumor cell types and found that RUNX2 interacts with three distinct proteins that respond to DNA damage -RU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Of particular interest, many RUNX2 target genes involved in cell migration, adhesion, and proliferation are upregulated upon WWOX loss in human OS (27). Proteomic studies recently showed that RUNX2 forms functional complexes with several proteins to mount an integrated response to DNA damage (39). Our results lead us to speculate that WWOX has differential effects on RUNX2 binding at promoters of selected genes.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest, many RUNX2 target genes involved in cell migration, adhesion, and proliferation are upregulated upon WWOX loss in human OS (27). Proteomic studies recently showed that RUNX2 forms functional complexes with several proteins to mount an integrated response to DNA damage (39). Our results lead us to speculate that WWOX has differential effects on RUNX2 binding at promoters of selected genes.…”
Section: Discussionmentioning
confidence: 99%
“…important inhibitor of estrogen signaling and stimulates oncogenic pathways. RUNX2 is a transcription factor involved in regulating cell determination (Young et al 2007;Blyth et al 2010) and the TGF-β and Wnt/β-catenin pathways (which are also involved in cancer development, progression, and metastasis) (Young et al 2007;Yang et al 2015) and opposes ER signaling, leading to more aggressive ER + breast cancer (Tandon et al 2014). Interestingly, recent studies have also shown that RUNX2 plays a crucial role in regulating mammary stem cell regeneration (Ferrari et al 2015).…”
Section: Identification Of Mrnas Highly Dependent On Overexpression Omentioning
confidence: 99%
“…Recently, we have also observed a similar phenomenon under 2D cultures demonstrating that depletion of RUNX2 in MiaPaCa-2 cells increased the accumulation of γH2AX following GEM or SAHA exposure (14,31), indicating that RUNX2 attenuated the expansion of DNA lesions irrespective of 2D or 3D culture systems. Notably, Yang et al (32) described that RUNX2 binds to γH2AX and siRNA-mediated knockdown of RUNX2 increases γH2AX in response to UV. Further studies are required to elucidate the functional significance of RUNX2/γH2AX interaction during DNA damage response.…”
Section: Discussionmentioning
confidence: 99%